Identification of Uptake Mechanism of Cell-Penetrating Peptides by their Polar Profile - Polanco, Carlos; Lino Samaniego Mendoza, José; Buhse, Thomas; Alberto Castañón González, Jorge; Gimbel, Arturo; Leopold Sordo, Marili (Current Bioinformatics, 2015)
In the recent years, so-called cell-penetrating peptides (CPPs) have been in constant study due to its ability to penetrate cell membranes. CCPs are characterized by a length of less than 60 amino acids, its highly cationic nature and by a positive net charge at neutral pH. For the CPPs either an endocytic or non-endocytic uptake mechanism has been identified. This work presents the computational polarity index method that is able to predict the uptake mechanism of CPPs with an accuracy of 72% in a double-blind test. This was achieved by reading the peptide sequence and measuring the polarity as one single physico-chemical property. The method was verified by extracting all peptides from the CPPsite database (April 21, 2014) and its efficiency was tested with seven specialized databases of peptides and proteins.
Keywords: endocytic pathway